2020
DOI: 10.3390/pathogens9070592
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium bovis Population Structure in Cattle and Local Badgers: Co-Localisation and Variation by Farm Type

Abstract: Bovine tuberculosis surveillance in Northern Ireland includes Multiple-Locus Variable number tandem repeat Analysis (MLVA) to determine the Mycobacterium bovis genetic type present in both cattle and the predominant wildlife host, the European badger (Meles meles). These data are useful for investigating clusters of infection and understanding the scale at which interspecific transmission may occur. We utilised a comprehensive dataset of routinely sampled isolates from infected cattle and from badgers killed i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Previous molecular studies from NI have revealed considerable spatial clustering of M. bovis genetic types in host populations, thereby affirming the important role of geographically localised processes in maintaining the bTB epidemic [ 35 , 36 , 37 , 38 ]. Although NI’s highly fragmented farmland is thought to be a contributing factor hampering eradication efforts, no studies to date have explored farm fragmentation as a risk factor for bTB, necessitating a deeper delve into the role of farm fragmentation as a facilitator of localised disease spread.…”
Section: Discussionmentioning
confidence: 93%
“…Previous molecular studies from NI have revealed considerable spatial clustering of M. bovis genetic types in host populations, thereby affirming the important role of geographically localised processes in maintaining the bTB epidemic [ 35 , 36 , 37 , 38 ]. Although NI’s highly fragmented farmland is thought to be a contributing factor hampering eradication efforts, no studies to date have explored farm fragmentation as a risk factor for bTB, necessitating a deeper delve into the role of farm fragmentation as a facilitator of localised disease spread.…”
Section: Discussionmentioning
confidence: 93%
“…This suggests that on the whole, the majority of individual fragments are in relatively close proximity to each other and the registered farmstead address. We would suggest, therefore, that at broad spatial scales (eg (Milne et al, 2020), the error introduced by imprecise herd locations may be minimal. For studies taking place at much smaller spatial extents, however, the discrepancies introduced from spatial irregularities may be of greater consequence.…”
Section: Discussionmentioning
confidence: 98%
“…Their study suggested that contaminated environment, such as at animal aggregation sites, played pivotal roles in the infection of MTBC in wild rodents and wild boars. In the United Kingdom and Ireland, researchers used GPS collars on cattle and badgers to track their activities and found that the direct contact between cattle and wild animals is actually fairly limited, indicating that direct transmission of tuberculosis may not be the main mechanism of interspecies transmission, implying the elevating possibility of indirect transmission through a contaminated shared environment ( 29 , 30 ). In Michigan US, there is evidence that MTBC in the environment of feed contaminated by wild deer suffering from tuberculosis can also cause tuberculosis in cattle, and this has been further confirmed in the laboratory ( 31 ).…”
Section: The Mycobacterium Tuberculosis Complex In...mentioning
confidence: 99%